Serial echocardiographic left ventricular ejection fraction measurements: A tool for detecting thalassemia major patients at risk of cardiac death - Aurelio Maggio (2018)
Cardiac damage remains a major cause of mortality among patients with thalassemia major. The detection of a lower cardiac magnetic resonance T2* (CMR-T2*) signal has been suggested as a powerful predictor of the subsequent development of heart failure. However, the lack of worldwide availability of CMR-T2* facilities prevents its widespread use for follow-up evaluations of cardiac function in thalassemia major patients, warranting the need to assess the utility of other possible procedures. In this setting, the determination of left ventricular ejection fraction (LVEF) offers an accurate and reproducible method for heart function evaluation. These findings suggest a reduction in LVEF ≥ 7%, over time, determined by 2-D echocardiography, may be considered a strong predictive tool for the detection of thalassemia major patients with increased risk of cardiac death. The reduction of LVEF ≥ 7% had higher (84.76%) predictive value. Finally, Kaplan-Meier survival curves of thalassemia major patients with LVEF ≥ 7% showed a statistically significant decreased probability of survival for heart disease (p = 0.0022). However, because of limitations related to the study design, such findings should be confirmed in a large long-term prospective clinical trial. © 2012 Elsevier Inc.